Rapid preparation method of large-size CuSn / Nb combined blank with good interface matching
Through fluidized bed drying and electron beam selection melting molding combined with electrochemical polishing technology, large-size CuSn/Nb combined blanks with good interface matching were prepared, which solved the problems of low preparation efficiency, poor mechanical properties and serious mass loss in the prior art, and significantly improved the performance of Nb3Sn superconducting wires.
Patent Information
- Application Number
- CN202411969985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
In the preparation of large-size CuSn/Nb combination blanks, the existing technology has problems such as low preparation efficiency, poor mechanical properties, inaccurate through-hole positioning and serious mass loss, which affects the performance of Nb3Sn superconducting wires.
The CuSn alloy powder was dried by fluidized bed drying method, and then the porous large-size CuSn alloy blank was obtained by melting and molding through electron beam selection zones, and the surface was treated using electrochemical polishing technology. Finally, the Nb rod was inserted to achieve a large-size CuSn/Nb combination blank with good interface coordination.
The rapid preparation of large-size CuSn/Nb combined blanks is achieved, which improves the density and mechanical properties of the blank, reduces through-hole positioning errors and mass losses, and improves the superconducting performance of Nb3Sn superconducting wires.
Smart Images

Figure CN119657946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electron beam selective melting and relates to a method for quickly preparing a large-size CuSn / Nb composite billet with good interface matching. Background Art
[0002] Nb3Sn low-temperature superconducting material has a superconducting transition temperature of 18.3K, an upper critical magnetic field of 25T and a high field strength of more than 10 6 A / cm 2 Due to its high critical current density and other advantages, it is widely used in quantum computing, high-field thermonuclear fusion reactors, nuclear magnetic resonance spectrometers, and large hadron colliders.
[0003] The process of preparing Nb3Sn superconducting wire by bronze method is as follows: first, the large-sized CuSn / Nb composite billet is hot extruded and drawn to obtain the CuSn / Nb hexagonal subcomponent structure, and then it is wound into a coil after truncation, reorganization, bundle drawing and intermediate annealing, and finally the Nb3Sn superconducting wire is obtained through long-term phase heat treatment.
[0004] At present, there are the following problems in the preparation process of large-sized CuSn / Nb composite billets: the preparation efficiency of large-sized CuSn alloy billets is low, the through-hole processing process takes 5 to 7 days, and the mechanical properties are still not enough to meet the requirements of coordinated deformation of large-sized CuSn alloy billets and Nb rods in the preparation process of Nb3Sn superconducting wires, and it is very easy to break during the drawing process. The through-hole processing process of large-sized CuSn alloy billets is affected by the precision of machine tools and human factors. There is a problem of inaccurate through-hole positioning, which will lead to uneven distribution of the generated Nb3Sn superconducting phase and inconsistent layer thickness, thereby affecting the critical current density of the wire and causing unstable superconducting performance; and the uneven stress distribution will cause local mechanical strength weakening and increase the risk of material cracking. The through-hole processing process will cause 25% to 39% mass loss of CuSn alloy billets, and the inner wall roughness of the machined alloy through-hole is high. It is difficult for Nb rods to achieve close mechanical bonding with porous CuSn alloy billets, affecting their interface connection and the generation of Nb3Sn superconducting phases. Summary of the invention
[0005] The purpose of the present invention is to provide a method for quickly preparing a large-sized CuSn / Nb composite billet with good interface matching, which solves the problems of low density, poor mechanical properties, inaccurate through-hole positioning and serious alloy waste in the preparation process of the porous large-sized CuSn alloy billet prepared by the prior art.
[0006] The technical solution adopted by the present invention is a method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching, and the specific steps are as follows: Step 1, using a fluidized bed drying method to dry the CuSn alloy powder in a specific particle size range to obtain a dried CuSn alloy powder; Step 2, subjecting the dried CuSn alloy powder to electron beam selective melting and forming to obtain a porous large-sized CuSn alloy blank; Step 3: Surface treatment of the prepared porous large-sized CuSn alloy body is performed using an electrochemical polishing technique to obtain a treated porous large-sized CuSn alloy body; Step 4: inserting the Nb rod into the processed porous large-sized CuSn alloy blank to obtain a large-sized CuSn / Nb composite blank with good interface matching.
[0007] The present invention is also characterized in that: The CuSn alloy powder with a specific particle size range in step 1 has a particle size of 50-106 μm, a fluidity of 17.98 s / 50 g-19.88 s / 50 g, and an apparent density of 4.25-4.67 g / cm 3 .
[0008] The specific method for drying the alloy powder in step 1 is as follows: placing the CuSn alloy powder in a fluidized bed, slowly and continuously introducing argon for 40 minutes, exhausting the air in the furnace, then closing the gas outlet, continuing to introduce argon, setting the heating furnace temperature to 150-200°C, the fluidization speed to 0.1-0.6 m / s, and the fluidization time to 40-140 minutes. After the heating is completed, continue to introduce argon to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0009] The specific steps of step 2 are: Step 2.1, create a model. The number of through holes in the porous large-size CuSn alloy blank model is 1 to 91, the through hole diameter is 5 to 12 mm, the alloy blank diameter is 20 to 160 mm, the preset printing height is 50 to 150 mm, the model is sliced and layered, and the slice layer thickness is 55 to 80 μm. Then, the preset model is imported into the electron beam selective melting molding equipment; Step 2.2: Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and evacuate the chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 1.5 Pa, and the electron beam was centered 3 minutes later to ensure that the electron beam was in the center of the substrate, and the current power was gradually adjusted to stabilize the gate voltage; Step 2.3, preheat the substrate to 350-400°C by electron beam scanning, and keep it warm for 35-60 minutes. After the preheating, spread the powder by scraper, and preheat the powder after spreading. Control the electron beam spot diameter to 100-225 μm for scanning, and then perform electron beam selective melting and molding. After printing, the porous large-size CuSn alloy blank is slowly cooled to room temperature in a continuous vacuum and atmosphere protection environment to obtain a high-performance porous large-size CuSn alloy blank.
[0010] In the electron beam selective melting process in step 2.3, the powder spreading coefficient is 60~85%, the scraper rate is 100~200mm / s, the powder preheating scanning current is 13~21mA, and the preheating time is 3~8s; the primary melting electron beam current is 4~6mA, the primary melting electron beam scanning speed is 4.2~5m / s, the secondary melting electron beam current is 9~14mA, the secondary melting electron beam scanning speed is 1.5~3.5m / s, the spacing between the two melting scans is 0.8~1.3mm, the defocus is 0.05~0.35mm, and a layer-by-layer rotation of 90° and remelting scanning strategy are adopted.
[0011] In step 2.3, the substrate temperature is maintained between 430 and 470 °C during the electron beam selective melting process, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, with the control ranges of 9 to 16 mA and 3 to 9 s, respectively. After printing, the porous large-sized CuSn alloy blank is slowly cooled to room temperature in a continuous vacuum and atmosphere protection environment to obtain a high-performance porous large-sized CuSn alloy blank. The specific process of step 3 is: After the porous large-sized CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out by high-pressure gas to obtain a porous large-sized CuSn alloy blank with a clean surface; the porous large-sized CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 70-76% sulfuric acid solution, 11-15% phosphoric acid solution and 13-15% anhydrous ethanol, the voltage is 4-9V, the current density is 11-16A / dm², the polishing time is 2-15min, and the electrolyte temperature is controlled at 20-30℃.
[0012] The specific process of step 4 is: immerse the Nb rod in liquid nitrogen for 3 to 5 minutes, and then insert it into the porous large-sized CuSn alloy blank.
[0013] The beneficial effects of the present invention are: (1) The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching of the present invention adopts a fluidized bed drying method, and heat and moisture transfer between the material and the gas is carried out under the protection of an argon atmosphere, so as to achieve uniform drying of the CuSn alloy powder and suppress the problem of powder refractory caused by moisture oxidation of the powder; at the same time, the fluidity of the powder is improved, adhesion or agglomeration between powder particles is prevented, and the consistency and uniform spreading of the powder layer density are ensured; the interference of moisture on the molding process is reduced, and energy consumption is reduced; (2) The invention discloses a method for rapidly preparing a large-sized CuSn / Nb composite blank with good interface matching. During the printing process, a 2×10 -2 The high vacuum degree of Pa and the introduction of helium protection can effectively prevent the oxidation of CuSn alloy powder and porous large-sized CuSn alloy blank in the powder bin, improve the purity and performance of the material, greatly enhance the transmission efficiency of electron beam energy and effectively prevent electron beam scattering; the direct-heated tungsten cathode is used to generate thermal electron radiation, and the 60kV output power of the electron beam is almost completely absorbed, with an energy utilization rate of more than 96%, which can effectively use CuSn alloy powder in a large particle size range for electron beam selective melting and molding, significantly reducing the cost of raw materials and improving production efficiency; preheating the substrate and powder during printing can effectively avoid the powder collapse phenomenon caused by electron beam bombardment of metal powder, which helps to enhance the bonding between powder particles. The combination of the substrate temperature and the temperature of the molten pool can reduce the formation of voids and cracks and improve the density of the printed parts; the substrate temperature is controlled between 430 and 470 ° C, and the material is in a high-temperature self-tempering state throughout the process, which is conducive to the dissolution of the tin-rich phase, laying a good microstructural foundation, eliminating the residual stress of the material, preventing deformation and cracking, promoting the uniform spreading of the molten pool, and improving the density and surface flatness of the material; multi-parameter coordinated regulation is carried out during the printing process, and a layer-by-layer rotation of 90° and a remelting scanning strategy are adopted to effectively inhibit the intergranular segregation of Sn, which is beneficial to control the grain texture and molten pool morphology in the material, reduce the generation of defects such as voids and unfused, improve the density of the printed parts, reduce the residual stress caused by local heat accumulation, and avoid the generation of local microcracks; (3) The present invention provides a method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching, wherein an electrochemical polishing device is used to polish a porous large-sized CuSn alloy billet. The electrochemical polishing generates an electric field by applying a potential difference, so that the raised portions of the surface and inner pores of the porous large-sized CuSn alloy billet are selectively dissolved due to a higher current density, thereby flattening the surface and inner pores. The treated smooth surface can improve the subsequent insertion effect of the Nb rod, achieve good matching between the Nb rod and the inner pore, reduce the pores at the interface, and thus reduce defects such as pores inside the wire in the subsequent phase formation process, thereby improving the superconducting performance of the wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1Schematic diagram of the structure of a large-sized CuSn / Nb composite billet with good interface matching in Example 3 of the present invention; Figure 2 This is the microstructure morphology of the porous large-sized CuSn alloy blank in Example 3 of the present invention; Figure 3 is the density variation curve of the porous large-size CuSn alloy blank in Examples 1 to 6 of the present invention; Figure 4 is the inner hole roughness variation curve of the porous large-size CuSn alloy blank in Examples 1 to 6 of the present invention; Figure 5 It is the stress-strain curve of the porous large-sized CuSn alloy blank in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION
[0015] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0016] A method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching, the specific steps are as follows: Step 1: The powder has a particle size of 50-106 μm, a fluidity of 17.98 s / 50 g-19.88 s / 50 g, and a bulk density of 4.25-4.67 g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace, then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 150~200℃, the fluidization speed is 0.1~0.6m / s, and the fluidization time is 40~140min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat transfer and moisture transfer between the CuSn alloy powder and the gas are carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0017] Step 2: subjecting the dried CuSn alloy powder to electron beam selective melting to obtain a porous large-sized CuSn alloy blank. The specific steps are as follows: Step 2.1, create a model. The number of through holes in the porous large-size CuSn alloy blank model is 1 to 91, the through hole diameter is 5 to 12 mm, the alloy blank diameter is 20 to 160 mm, the preset printing height is 50 to 150 mm, the model is sliced and layered, and the slice layer thickness is 55 to 80 μm. Then, the preset model is imported into the electron beam selective melting molding equipment; Step 2.2: Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 1.5 Pa, and the electron beam was centered 3 minutes later to ensure that the electron beam was in the center of the substrate, and the current power was gradually adjusted to stabilize the gate voltage; Step 2.3, preheat the substrate to 350-400°C by electron beam scanning, keep warm for 35-60 minutes, spread powder by scraper after preheating, preheat the powder after spreading, control the electron beam spot diameter to 100-225μm for scanning, and then perform electron beam selective melting molding. After each layer of molding is completed, control the substrate to descend and use electron beam scanning for thermal compensation and then spread powder again to mold the next layer. The electron beam action range of the powder preheating, electron beam molding, and thermal compensation covers the entire powder bed.
[0018] During the electron beam selective melting molding process, the powder spreading coefficient is 60~85%, the scraper rate is 100~200mm / s, the powder preheating scanning current is 13~21mA, and the preheating time is 3~8s; the primary melting electron beam current is 4~6mA, the primary melting electron beam scanning speed is 4.2~5m / s, the secondary melting electron beam current is 9~14mA, the secondary melting electron beam scanning speed is 1.5~3.5m / s, the spacing between the two melting scans is 0.8~1.3mm, the defocus is 0.05~0.35mm, and a layer-by-layer rotation of 90° and remelting scanning strategy are adopted.
[0019] During the electron beam selective melting process, the substrate temperature is kept between 430 and 470 ° C, and the preheating power and preheating time are adjusted in a gradient manner in combination with the actual vertical printing height, with the adjustment ranges of 9 to 16 mA and 3 to 9 seconds, respectively. After printing, the porous large-sized CuSn alloy blank is slowly cooled to room temperature in a continuous vacuum and atmosphere protection environment to obtain a high-performance porous large-sized CuSn alloy blank.
[0020] The printing process uses a 2×10 -2The high vacuum degree of Pa and the introduction of helium protection can effectively prevent the oxidation of CuSn alloy powder and porous large-sized CuSn alloy blank in the powder bin, improve the purity and performance of the material, greatly enhance the transmission efficiency of electron beam energy and effectively prevent electron beam scattering; the direct-heated tungsten cathode is used to generate thermal electron radiation, and the 60kV output power of the electron beam is almost completely absorbed, with an energy utilization rate of more than 96%, which can effectively use CuSn alloy powder in a large particle size range for electron beam selective melting and molding, significantly reducing the cost of raw materials and improving production efficiency; preheating the substrate and powder during printing can effectively avoid the powder collapse phenomenon caused by electron beam bombardment of metal powder, which helps to enhance the bonding between powder particles. The combination of the substrate temperature and the molten pool temperature can reduce the formation of voids and cracks and improve the density of the printed parts; the substrate temperature is controlled between 430 and 470 ° C, and the material is in a high-temperature self-tempering state throughout the process, which is conducive to the dissolution of the tin-rich phase, laying a good microstructural foundation, eliminating the residual stress of the material, preventing deformation and cracking, promoting the uniform spreading of the molten pool, and improving the density and surface smoothness of the material; multi-parameter coordinated regulation is carried out during the printing process, and a layer-by-layer rotation of 90 ° and a remelting scanning strategy are adopted to effectively inhibit the intergranular segregation of Sn, which is beneficial to control the grain texture and molten pool morphology in the material, reduce the generation of defects such as voids and unfused, improve the density of the printed parts, reduce the residual stress caused by local heat accumulation, and avoid the generation of local microcracks.
[0021] Step 3: Surface treatment of the prepared porous large-sized CuSn alloy body is performed using electrochemical polishing technology to obtain a treated porous large-sized CuSn alloy body. The specific process is as follows: After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 70-76% sulfuric acid solution, 11-15% phosphoric acid solution and 13-15% anhydrous ethanol, the voltage is 4-9V, the current density is 11-16A / dm², the polishing time is 2-15min, and the electrolyte temperature is controlled at 20-30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0022] Step 4: Immerse the Nb rod in liquid nitrogen for 3 to 5 minutes to fully cool it, so as to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0023] The invention discloses a method for rapidly preparing a large-sized CuSn / Nb composite blank with good interface matching. Through the coordinated control of multiple parameters in the electron beam selective melting process, the four processes of preheating, melting, solidification and high-temperature self-tempering are realized during the printing process. The cooling rate of solidification in the electron beam selective melting molding is as high as 10 5 ℃ / s, which is conducive to suppressing the segregation of large-sized tin-rich phases; preheating the substrate and powder bed can effectively avoid the powder collapse phenomenon caused by electron beam bombardment of metal powders, which helps to enhance the bonding between powder particles; the whole forming process is in a high-temperature self-tempering state, which can promote the dissolution of tin-rich phases, effectively relieve stress concentration, reduce macro warping and cracking tendencies, greatly improve the density of the alloy, and help to obtain a joint improvement in strength and plasticity. The preparation efficiency of porous large-sized CuSn alloy blanks is improved by electron beam selective melting technology. At the same time, by controlling electron beam parameters and combining electrochemical polishing technology, the forming of high-surface quality inner holes is achieved, the matching of the interface between the inner hole and the Nb rod is improved, and the interface pores are reduced, laying the foundation for the preparation of high-performance Nb3Sn superconducting wires.
[0024] Example 1 The powder particle size is 50~106μm, the fluidity is 18.83s / 50g, and the bulk density is 4.50g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 170°C, the fluidization speed is 0.3m / s, and the fluidization time is 80min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0025] To create a model, the porous large-size CuSn alloy billet model has 37 through holes, a through hole diameter of 10 mm, an alloy billet diameter of 110 mm, a preset printing height of 90 mm, and a printing time of 15.8 h. The model is sliced and layered with a slice layer thickness of 65 μm, and then the preset model is imported into the electron beam selective melting molding equipment.
[0026] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2Helium was introduced at 10 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0027] The substrate was preheated to 370℃ by electron beam scanning and kept warm for 50min. After preheating, powder was spread by scraper, the scraper speed was 140mm / s, the powder spreading coefficient was 75%, and the powder was preheated after spreading. The preheating electron beam current was 17mA, the preheating time was 6s, and the electron beam spot diameter was 150μm. Then, electron beam selective melting molding was performed; after each layer of molding was completed, the substrate was controlled to descend and the electron beam scanning was used for thermal compensation and then the powder was spread again to perform the next layer molding. During the printing process, the substrate temperature was controlled to be 450℃, and the preheating power and preheating time were gradient regulated in combination with the actual vertical printing height, and the regulation ranges were 11~15mA and 4~6s respectively. The specific parameters for controlling the electron beam selective melting molding are as follows: the melting electron beam current is 11mA, the melting electron beam scanning speed is 2.5m / s, the scanning spacing is 1mm, the defocus is 0.15mm, and the interlayer rotation 90° scanning strategy is adopted. After the electron beam selective melting forming is completed, the porous large-sized CuSn alloy blank is slowly cooled to room temperature in a vacuum and helium atmosphere protection environment.
[0028] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 74% sulfuric acid solution, 12% phosphoric acid solution and 14% anhydrous ethanol, the voltage is 6V, the current density is 13A / dm², the polishing time is 8min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0029] The density of the prepared porous large-sized CuSn alloy blank is 99.80%, the inner hole roughness is 18.61µm, and the roughness after polishing is 2.18µm. The tensile strength of the porous large-sized CuSn alloy blank is 654MPa and the elongation after fracture is 50.07%.
[0030] The Nb rod is immersed in liquid nitrogen to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0031] Example 2 The powder particle size is 50~72μm, the fluidity is 19.88s / 50g, and the bulk density is 4.67g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 150°C, the fluidization speed is 0.1m / s, and the fluidization time is 40min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0032] The model was created. The porous large-size CuSn alloy billet model had 7 through holes, a through hole diameter of 6 mm, an alloy billet diameter of 40 mm, a preset printing height of 50 mm, and a printing time of 8.7 h. The model was sliced and layered with a slice layer thickness of 55 μm, and then the preset model was imported into the electron beam selective melting molding equipment.
[0033] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 10 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0034] The substrate is preheated to 350℃ by electron beam scanning and kept warm for 60min. After preheating, the powder is spread by a scraper, the scraper speed is 100mm / s, the powder spreading coefficient is 85%, and the powder is preheated after spreading. The preheating electron beam current is 13mA, the preheating time is 8s, and the electron beam spot diameter is 100μm. Then the electron beam selective melting molding is performed; after each layer of molding is completed, the substrate is controlled to descend and the electron beam scanning is used for thermal compensation and then the powder is spread again to form the next layer. During the printing process, the substrate temperature is controlled to 430℃, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, and the control range is 9~13mA and 6~8s respectively. The parameters for controlling the electron beam selective melting are as follows: the electron beam current for the first melting is 4.0 mA, the electron beam scanning speed for the first melting is 4.2 m / s, the electron beam current for the second melting is 9 mA, and the electron beam scanning speed for the second melting is 1.5 m / s; the interval between the two melting scans is 0.8 mm, the defocus amount is 0.05 mm, and a remelting scanning strategy is adopted. After the electron beam selective melting is completed, the porous large-size CuSn alloy blank is slowly cooled to room temperature with the furnace under a continuous vacuum and atmosphere protection environment.
[0035] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 70% sulfuric acid solution, 15% phosphoric acid solution and 15% anhydrous ethanol, the voltage is 4V, the current density is 11A / dm², the polishing time is 4min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0036] The density of the prepared porous large-sized CuSn alloy blank is 99.91%, the inner hole roughness is 16.19µm, and the roughness after polishing is 2.05µm. The tensile strength of the porous large-sized CuSn alloy blank is 559MPa and the elongation after fracture is 60.98%.
[0037] The Nb rod is immersed in liquid nitrogen to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0038] Example 3 The powder particle size is 70~106μm, the fluidity is 18.31s / 50g, and the bulk density is 4.46g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 180°C, the fluidization speed is 0.4m / s, and the fluidization time is 100min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0039] The model was created. The porous large-size CuSn alloy billet model had 61 through holes, a through hole diameter of 12 mm, an alloy billet diameter of 150 mm, a preset printing height of 130 mm, and a printing time of 22.8 h. The model was sliced and layered with a slice layer thickness of 70 μm, and then the preset model was imported into the electron beam selective melting molding equipment.
[0040] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 10 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0041] The substrate is preheated to 380°C by electron beam scanning and kept warm for 45 minutes. After preheating, the powder is spread by a scraper with a scraper speed of 160 mm / s and a powder spreading coefficient of 70%. After spreading the powder, the powder is preheated with a preheating electron beam current of 19 mA and a preheating time of 5 seconds. Then, electron beam selective melting molding is performed with an electron beam spot diameter of 175 μm. After each layer of molding is completed, the substrate is controlled to descend and electron beam scanning is used for thermal compensation before powder is spread again for the next layer of molding. During the printing process, the substrate temperature is controlled to 460°C, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, with the control ranges of 12~16 mA and 3~5 seconds respectively. The parameters for controlling the electron beam selective melting molding are as follows: the electron beam current for the first melting is 5 mA, the electron beam scanning speed for the second melting is 4.6 m / s, the electron beam current for the second melting is 12 mA, the electron beam scanning speed for the second melting is 3 m / s, the interval between the two melting scans is 1.1 mm, the defocus amount is 0.2 mm, and a remelting scanning strategy is adopted. After the electron beam selective melting molding is completed, the porous large-size CuSn alloy blank is slowly cooled to room temperature with the furnace under a continuous vacuum and atmosphere protection environment.
[0042] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 76% sulfuric acid solution, 11% phosphoric acid solution and 13% anhydrous ethanol, the voltage is 7V, the current density is 14A / dm², the polishing time is 10min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0043] The density of the prepared porous large-sized CuSn alloy blank is 99.82%, the inner hole roughness is 16.99µm, and the roughness after polishing is 2.39µm. The tensile strength of the porous large-sized CuSn alloy blank is 669MPa and the elongation after fracture is 52.05%.
[0044] The Nb rod is immersed in liquid nitrogen to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0045] Figure 1Schematic diagram of the structure of a high-performance large-size CuSn / Nb composite billet with good interface matching in this embodiment; Figure 2 This is the microstructure morphology of the CuSn alloy blank in this embodiment. It can be seen that the residual δ phase content in the structure is relatively small, and the internal structure shows alternating distribution of fine grain areas and coarse grain areas. The boundary of the molten pool is the fine grain area, and the center of the molten pool is the coarse grain area.
[0046] Example 4 The powder particle size is 50~96μm, the fluidity is 19.21s / 50g, and the bulk density is 4.52g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 160°C, the fluidization speed is 0.2m / s, and the fluidization time is 60min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0047] To create a model, the porous large-size CuSn alloy billet model has 19 through holes, a through hole diameter of 8 mm, an alloy billet diameter of 80 mm, a preset printing height of 60 mm, and a printing time of 10.5 h. The model is sliced and layered with a slice layer thickness of 60 μm, and then the preset model is imported into the electron beam selective melting molding equipment.
[0048] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 120 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0049] The substrate is preheated to 360°C by electron beam scanning and kept warm for 55 minutes. After preheating, the powder is spread by a scraper with a scraper speed of 120 mm / s and a powder spreading coefficient of 80%. After spreading the powder, the powder is preheated with a preheating electron beam current of 15 mA and a preheating time of 7 seconds. Then, electron beam selective melting molding is performed with an electron beam spot diameter of 125 μm. After each layer of molding is completed, the substrate is controlled to descend and electron beam scanning is used for thermal compensation before powder is spread again for the next layer of molding. During the printing process, the substrate temperature is controlled to 440°C, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, with the control ranges of 10~14 mA and 5~7 seconds respectively. The parameters for controlling the electron beam selective melting are as follows: the electron beam current for the first melting is 4.5 mA, the electron beam scanning speed for the second melting is 4.4 m / s, the electron beam current for the second melting is 10 mA, the electron beam scanning speed for the second melting is 2 m / s, the interval between the two melting scans is 0.9 mm, the defocus amount is 0.1 mm, and a remelting scanning strategy is adopted. After the electron beam selective melting is completed, the porous large-size CuSn alloy blank is slowly cooled to room temperature with the furnace under a continuous vacuum and atmosphere protection environment.
[0050] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 72% sulfuric acid solution, 13% phosphoric acid solution and 15% anhydrous ethanol, the voltage is 5V, the current density is 12A / dm², the polishing time is 6min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0051] The density of the prepared porous large-sized CuSn alloy blank is 99.76%, the inner hole roughness is 19.26µm, and the roughness after polishing is 2.44µm. The tensile strength of the porous large-sized CuSn alloy blank is 682MPa and the elongation after fracture is 41.04%.
[0052] The Nb rod is immersed in liquid nitrogen to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0053] Example 5 The powder particle size is 60~106μm, the fluidity is 18.12s / 50g, and the bulk density is 4.39g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 190°C, the fluidization speed is 0.5m / s, and the fluidization time is 120min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0054] To create a model, the porous large-size CuSn alloy billet model has 1 through hole, a through hole diameter of 5 mm, an alloy billet diameter of 20 mm, a preset printing height of 100 mm, and a printing time of 6.5 h. The model is sliced and layered with a slice layer thickness of 75 μm, and then the preset model is imported into the electron beam selective melting molding equipment.
[0055] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 120 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0056] The substrate is preheated to 390°C by electron beam scanning and kept warm for 40 minutes. After preheating, the powder is spread by a scraper with a scraper speed of 180 mm / s and a powder spreading coefficient of 65%. After spreading the powder, the powder is preheated with a preheating electron beam current of 20 mA and a preheating time of 4 seconds. Then, electron beam selective melting molding is performed with an electron beam spot diameter of 200 μm. After each layer of molding is completed, the substrate is controlled to descend and electron beam scanning is used for thermal compensation before powder is spread again for the next layer of molding. During the printing process, the substrate temperature is controlled to 465°C, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, with the control ranges of 13~15 mA and 6~9 seconds respectively. The parameters for controlling the electron beam selective melting are as follows: the electron beam current for the first melting is 5.5 mA, the electron beam scanning speed for the second melting is 4.8 m / s, the electron beam current for the second melting is 13 mA, the electron beam scanning speed for the second melting is 3.2 m / s, the scanning interval between the two meltings is 1.2 mm, the defocusing amount is 0.3 mm, and a remelting scanning strategy is adopted. After the electron beam selective melting is completed, the porous large-size CuSn alloy blank is slowly cooled to room temperature with the furnace under a continuous vacuum and atmosphere protection environment.
[0057] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 71% sulfuric acid solution, 15% phosphoric acid solution and 14% anhydrous ethanol, the voltage is 8V, the current density is 15A / dm², the polishing time is 5min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0058] The density of the prepared porous large-sized CuSn alloy blank is 99.93%, the inner hole roughness is 17.12µm, and the roughness after polishing is 2.30µm. The tensile strength of the porous large-sized CuSn alloy blank is 613MPa and the elongation after fracture is 62.27%.
[0059] The Nb rod is immersed in liquid nitrogen to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0060] Example 6 The powder particle size is 80~106μm, the fluidity is 17.98s / 50g, and the bulk density is 4.25g / cm 3 The CuSn alloy powder is placed on the perforated plate of the fluidized bed dryer, the gas outlet is opened, and argon is slowly and continuously introduced from the bottom for 40 minutes to exhaust the air in the furnace. Then the gas outlet is closed, and argon is continued to be introduced. The heating furnace temperature is set to 200°C, the fluidization speed is 0.6m / s, and the fluidization time is 140min. The CuSn alloy powder moves on the gas distribution plate and is suspended in the argon gas flow. Heat and moisture transfer between the CuSn alloy powder and the gas is carried out to achieve uniform heat exchange. After the heating is completed, argon is continuously introduced to cool the CuSn alloy powder to room temperature in an argon atmosphere.
[0061] The model was created. The porous large-size CuSn alloy billet model had 91 through holes, a through hole diameter of 9 mm, an alloy billet diameter of 160 mm, a preset printing height of 150 mm, and a printing time of 26.7 h. The model was sliced and layered with a slice layer thickness of 80 μm, and then the preset model was imported into the electron beam selective melting molding equipment.
[0062] Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and fill it under the substrate. Fix and level the substrate and scraper to ensure that the thermocouple is in good contact with the substrate, and close the bin door. Evacuate the gun chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 10 Pa, and the electron beam was centered after 3 minutes to ensure that the electron beam was in the center of the substrate. The current power was gradually adjusted to stabilize the gate voltage.
[0063] The substrate is preheated to 400℃ by electron beam scanning and kept warm for 35 minutes. After preheating, the powder is spread by a scraper with a scraper speed of 200mm / s and a powder spreading coefficient of 60%. After spreading the powder, the powder is preheated with a preheating electron beam current of 21mA and a preheating time of 3s. Then, electron beam selective melting molding is performed with an electron beam spot diameter of 225μm. After each layer of molding is completed, the substrate is controlled to descend and electron beam scanning is used for thermal compensation before powder is spread again for the next layer of molding. During the printing process, the substrate temperature is controlled to 470℃, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, with the control ranges of 14~16mA and 7~9s respectively. The parameters for controlling the electron beam selective melting are as follows: the electron beam current for the first melting is 6 mA, the electron beam scanning speed for the second melting is 5 m / s, the electron beam current for the second melting is 14 mA, the electron beam scanning speed for the second melting is 3.5 m / s, the scanning interval between the two meltings is 1.3 mm, the defocusing amount is 0.35 mm, and a remelting scanning strategy is adopted. After the electron beam selective melting is completed, the porous large-size CuSn alloy blank is slowly cooled to room temperature with the furnace under a continuous vacuum and atmosphere protection environment.
[0064] After the porous large-size CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out with high-pressure gas to obtain a porous large-size CuSn alloy blank with no powder sticking and clean surface; the porous large-size CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 75% sulfuric acid solution, 11% phosphoric acid solution and 14% anhydrous ethanol, the voltage is 9V, the current density is 16A / dm², the polishing time is 15min, and the electrolyte temperature is controlled at 20~30℃ to ensure a stable reaction and obtain a porous large-size CuSn alloy blank with high surface quality.
[0065] The density of the prepared porous large-sized CuSn alloy blank is 99.88%, the inner hole roughness is 18.77µm, and the roughness after polishing is 2.54µm. The tensile strength of the porous large-sized CuSn alloy blank is 598MPa and the elongation after fracture is 59.44%.
[0066] The Nb rod was immersed in liquid nitrogen for 3 minutes to reduce the diameter of the Nb rod by utilizing its thermal shrinkage characteristics in an ultra-low temperature environment, so that it can be more easily inserted into the porous large-sized CuSn alloy blank. As the Nb rod returns to ambient temperature, its size returns to its original state, thereby achieving a tight mechanical interference fit in the porous large-sized CuSn alloy blank, and obtaining a high-performance large-sized CuSn / Nb composite blank with good interface fit.
[0067] Figure 3: is the density variation curve of the porous large-sized CuSn alloy blanks in Examples 1 to 6. It can be seen that the density of the porous large-sized CuSn alloy blanks is above 99.75%.
[0068] Figure 4 1 is a curve showing the change in inner hole roughness of the porous large-sized CuSn alloy blanks in Examples 1 to 6. It can be seen that the inner hole roughness of the porous large-sized CuSn alloy blanks fluctuates around 18.5µm and 2.3µm before and after polishing, respectively, and the change is relatively stable.
[0069] Figure 5 1 to 6, it can be seen that the mechanical properties of the porous large-sized CuSn alloy blank can meet the requirements of the coordinated deformation of the porous large-sized CuSn alloy blank and the Nb rod in the preparation process of the Nb3Sn superconducting wire.
Claims
1. A method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching, characterized in that: The specific steps are as follows: Step 1, using a fluidized bed drying method to dry the CuSn alloy powder in a specific particle size range to obtain a dried CuSn alloy powder; Step 2, subjecting the dried CuSn alloy powder to electron beam selective melting and forming to obtain a porous large-sized CuSn alloy blank; Step 3: Surface treatment of the prepared porous large-sized CuSn alloy body is performed using an electrochemical polishing technique to obtain a treated porous large-sized CuSn alloy body; Step 4: inserting the Nb rod into the processed porous large-sized CuSn alloy blank to obtain a large-sized CuSn / Nb composite blank with good interface matching.
2. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 1, characterized in that: The CuSn alloy powder in the specific particle size range in step 1 has a particle size of 50-106 μm, a fluidity of 17.98 s / 50 g-19.88 s / 50 g, and a bulk density of 4.25-4.67 g / cm 3 .
3. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 2, characterized in that: The specific method of drying the alloy powder in step 1 is: placing the CuSn alloy powder in a fluidized bed, slowly and continuously introducing argon for 40 minutes, exhausting the air in the furnace, then closing the air outlet, continuing to introduce argon, setting the heating furnace temperature to 150-200°C, the fluidization speed to 0.1-0.6 m / s, and the fluidization time to 40-140 minutes. After the heating is completed, continue to introduce argon to cool the CuSn alloy powder to room temperature in an argon atmosphere.
4. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 1, characterized in that: The specific steps of step 2 are: Step 2.1, create a model. The number of through holes in the porous large-size CuSn alloy blank model is 1 to 91, the through hole diameter is 8 mm, the alloy blank diameter is 70 to 200 mm, the preset printing height is 50 to 150 mm, the model is sliced and layered, and the slice layer thickness is 55 to 80 μm. Then, the preset model is imported into the electron beam selective melting molding equipment; Step 2.2: Place the dried CuSn alloy powder into the powder supply bin of the electron beam selective melting molding equipment and evacuate the chamber to a vacuum degree of 3×10 -5 Pa, the vacuum degree of the molding chamber is 2×10 -2 Helium was introduced at 1.5 Pa, and the electron beam was centered 3 minutes later to ensure that the electron beam was in the center of the substrate, and the current power was gradually adjusted to stabilize the gate voltage; Step 2.3, preheat the substrate to 350-400°C by electron beam scanning, and keep it warm for 35-60 minutes. After the preheating, spread the powder by scraper, and preheat the powder after spreading. Control the electron beam spot diameter to 100-225 μm for scanning, and then perform electron beam selective melting and molding. After printing, the porous large-size CuSn alloy blank is slowly cooled to room temperature in a continuous vacuum and atmosphere protection environment to obtain a high-performance porous large-size CuSn alloy blank.
5. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 4, characterized in that: In the electron beam selective melting molding process in step 2.3, the powder spreading coefficient is 60~85%, the scraper rate is 100~200mm / s, the powder preheating scanning current is 13~21mA, and the preheating time is 3~8s; the primary melting electron beam current is 4~6mA, the primary melting electron beam scanning speed is 4.2~5m / s, the secondary melting electron beam current is 9~14mA, the secondary melting electron beam scanning speed is 1.5~3.5m / s, the spacing between the two melting scans is 0.8~1.3mm, the defocus amount is 0.05~0.35mm, and a layer-by-layer rotation of 90° and a remelting scanning strategy are adopted.
6. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 4, characterized in that: In the step 2.3, the substrate temperature is maintained between 430 and 470°C during the electron beam selective melting process, and the preheating power and preheating time are gradient-controlled in combination with the actual vertical printing height, and the control ranges are 9 to 16 mA and 3 to 9 s, respectively. After printing is completed, the porous large-sized CuSn alloy blank is slowly cooled to room temperature in a continuous vacuum and atmosphere protection environment to obtain a high-performance porous large-sized CuSn alloy blank.
7. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 1, characterized in that: The specific process of step 3 is as follows: After the porous large-sized CuSn alloy blank obtained by electron beam selective melting is taken out, the residual CuSn alloy powder is blown out by high-pressure gas to obtain a porous large-sized CuSn alloy blank with a clean surface; the porous large-sized CuSn alloy blank is placed in an electrolytic cell as an anode, the cathode is made of stainless steel, the electrolyte composition is 70-76% sulfuric acid solution, 11-15% phosphoric acid solution and 13-15% anhydrous ethanol, the voltage is 4-9V, the current density is 11-16A / dm², the polishing time is 2-15min, and the electrolyte temperature is controlled at 20-30℃.
8. The method for rapidly preparing a large-sized CuSn / Nb composite billet with good interface matching according to claim 1, characterized in that: The specific process of step 4 is: immerse the Nb rod in liquid nitrogen for 3-5 minutes, and then insert it into the porous large-sized CuSn alloy blank.
Citation Information
Cited By
Method for controlling powder sticking phenomenon of porous metal in laser additive manufacturing
CN120755356A